THE ROLE OF FOREIGN INVESTMENT AND ITS IMPACT ON INTERNATIONAL MARKETING AND WORLD ECONOMIES-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT THE IRAQI INVESTMENT BANK, KARBALA BRANCH - Mayasa Nazim Aziz Muhammad (Galaxy International Interdisciplinary Research Journal, 2024)
The aim of the research is to identify the impact of foreign investment on the economies of the world, the impact of foreign investment on international marketing, to identify the role of foreign investment in comprehensive development in developing countries, while arriving at the most prominent obstacles to foreign investment, as many developing countries aim to build an economic base to obtain their position. In the global market in light of economic globalization and due to its broad scope, it strives to attract the largest possible amount of foreign capital, which has proven its flexibility in times of crises. Especially since foreign investors benefit host countries by bringing modern resources represented in marketing skills, technology, and even management, in addition to that they contribute significantly to increasing job opportunities and improving efficiency by increasing the level of internal competition among developing countries. The research dealt with the concept of foreign investment and its determinants. Foreign investment in addition to the definition of international marketing and its causes. The research used a simple random sampling method to select the study sample, which was represented by workers in the Iraqi Investment Bank, and its size reached 58 workers. The results of the study showed that foreign investment plays a role in the world's economies, and that foreign investment affects international marketing. It also showed that foreign investment plays a vital role in comprehensive development in developing countries. The most prominent obstacles to foreign investment in Iraq were economic obstacles. The research recommended working to readapt the investment climate. In Iraq, by activating laws related to investment and activating supervision, in addition to developing institutions in order to attract foreign investment, foreign investments must not affect national sovereignty, and must not affect political decisions regarding the terms of the contract between the host country and the owner of this investment.